Incidence of Multidrug-Resistant UTI - Abbasi, Maryam; Aziz, Khawaja Tahir; Abbasi, Amna (Indus Journal of Bioscience Research, 2025)
Background: Children are experiencing more difficult-to-manage UTIs as a result of the worldwide rise of multidrug-resistant pathogens. Methodology: It was a cross-sectional observational study. The study was conducted at Sheikh Khalifa Bin Zayed Al Nahyan/Combined Military Hospital, Muzaffarabad, Azad Jammu and Kashmir, Pakistan. 215 patients were included in the study. A standardized data collection questionnaire was used to collect data on biosociodemographics such as age, gender, and history of UTIs. Data analysis was done using IBM SPSS version 25. Chi-square was applied to find the association between MDR UTI and other variables such as the presence of UTI, antibiotic use, hospitalization requirement, as well as recurrent UTI. Multivariate logistic regression was applied to evaluate independent risk factors for MDR-UTI, which was expressed as adjusted Odds Ratios with 95% CI. Results: In this investigation on the epidemiology of multidrug-resistant UTI in children aged one to fifteen years, 53 percent were female, and 47 percent of cases were male, and all 104 multiple drug-resistant UTI cases fell into this category, indicating a significant correlation (p=0.00). Multiple drug-resistant UTI was substantially related to hospitalisation, since all 80 hospitalised patients had the condition (p-value = 0.00). gender (p-value = 0.767) was not a significant predictor of multiple drug-resistant urinary tract infection, and the unreliable model coefficients indicate potential data limitations. Conclusion: The study found a substantial link between multiple drug-resistant UTIs, hospitalization, and UTI presence. All multiple drug-resistant UTI cases were in children with confirmed UTI. through carbapenems were the most used antibiotics, there was no significant relationship between drug type and multiple drug-resistant UTI. These findings underline the importance of effectively preventing and managing multiple drug-resistant UTIs in pediatric patients.